Therapeutic targets and mechanism of hydroxysafflower yellow A on poststroke cognitive impairment: Network pharmacology, molecular docking and molecular dynamics simulation - Jiqin Tang; Guoxiu Zu; Ying Yu; Xijian Liu; Wei Guo; Zhiqi Sun; Tao Han; Hailiang Huang (Elsevier, 2022)
Objective: The aim of this study was to explore the therapeutic target and mechanism of Hydroxy Safflower Yellow A pigment (HSYA)-the main water-soluble component of Safflower-in the treatment of Poststroke Cognitive Impairment (PSCI) by network pharmacology and molecular docking methods. Method: GeneCards, PharmMapper, and Swiss Target Prediction databases were used to screen HSYA targets. Protein-Protein Interaction analysis, Gene Ontology, and KEGG enrichment analysis were performed through STRING and Metascape databases, respectively. Cytoscape 3.6.0 was used to draw the network diagram of the "HSYA-target-PSCI pathway." AutoDockVina was used for molecular docking. Results: A total of 310 targets of HSYA and 2455 potential targets of PSCI were screened, and the shared target was 159. After GO and KEGG enrichment analysis, HSYA was found to exhibit a therapeutic effect on PSCI by regulating various cancer pathways, endocrine regulation, cell proliferation, and apoptosis pathways. The molecular docking results suggest that HSYA has the best docking activity with the core target HRAS. Molecular dynamics simulation results showed that HSYA was the best binding agent to MAPK1, followed by HRAS. Conclusion: HSYA may regulate cell autophagy and apoptosis by regulating various pathways like PI3K-AKT and MAPK signaling pathways. It inhibits the secretion of inflammatory and angiogenic factors, inhibits endothelial angiogenesis, and plays a role in treating PSCI.